Law and practice of liability management : debt tender offers, exchange offers, bond buybacks and consent solicitations in international capital markets / Apostolos Ath. Gkoutzinis. - Gkoutzinis, Apostolos Ath (Cambridge University Press, 2013)
Tender offers, exchange offers and consent solicitations in connection with debt securities are important instruments of corporate restructurings, corporate rescues, recapitalisations and other types of liability management of public and private companies. Although tender offers for shares, stocks and other equity securities are covered by a vast literature on public mergers, takeovers and acquisitions, the literature on liability management transactions for debt securities is scarce. Law and Practice of Liability Management rectifies this by providing a systematic treatise of the law relating to this significant aspect of the global capital market. It guides students and professionals through the complex legal and regulatory requirements applicable to these transactions, the increasing regulatory interest by the world's leading financial regulatory authorities, and recent innovations in the structuring, legal techniques and execution of the relevant transactions in international capital markets.